Comparative Genomics of Thiohalobacter thiocyanaticus HRh1T and Guyparkeria sp. SCN-R1, Halophilic Chemolithoautotrophic Sulfur-Oxidizing Gammaproteobacteria Capable of Using Thiocyanate as Energy Source - Tsallagov, Stanislav I.; Sorokin, Dimitry Y.; Tikhonova, Tamara V.; Popov, Vladimir O.; Muyzer, Gerard (Frontiers in Microbiology, 2019)
The genomes of Thiohalobacter thiocyanaticus and Guyparkeria (formerly known as Halothiobacillus) sp. SCN-R1, two halophilic sulfur-oxidizing bacteria (SOB) capable of thiocyanate oxidation via the “cyanate pathway”, have been analyzed with a particular focus on their thiocyanate-oxidizing potential and sulfur oxidation pathways. Both genomes encode homologues of the enzyme thiocyanate dehydrogenase (TcDH) that oxidizes thiocyanate via the “cyanate pathway” in members of the haloalkaliphilic SOB of the genus Thioalkalivibrio. However, despite the presence of conservative motives indicative of TcDH, the putative TcDH of the halophilic SOB have a low overall amino acid similarity to the Thioalkalivibrio enzyme, and also the surrounding genes in the locus were different. In particular, an alternative copper transport system Cus is present instead of Cop and a putative zero-valent sulfur acceptor protein gene appears just before TcDH. Moreover, in contrast to the thiocyanate-oxidizing Thioalkalivibrio species, both genomes of the halophilic SOB contained a gene encoding the enzyme cyanate hydratase. The sulfur-oxidizing pathway in the genome of Thiohalobacter includes a Fcc type of sulfide dehydrogenase, a rDsr complex/AprAB/Sat for oxidation of zero-valent sulfur to sulfate, and an incomplete Sox pathway, lacking SoxCD. The sulfur oxidation pathway reconstructed from the genome of Guyparkeria sp. SCN-R1 was more similar to that of members of the Thiomicrospira-Hydrogenovibrio group, including a Fcc type of sulfide dehydrogenase and a complete Sox complex. One of the outstanding properties of Thiohalobacter is the presence of a Na+-dependent ATP synthase, which is rarely found in aerobic Prokaryotes. Overall, the results showed that, despite an obvious difference in the general sulfur-oxidation pathways, halophilic and haloalkaliphilic SOB belonging to different genera within the Gammaproteobacteria developed a similar unique thiocyanate-degrading mechanism based on the direct oxidative attack on the sulfane atom of thiocyanate.